A hydrolytically stable hydrogen-bonded inorganic-organic network as a luminescence turn-on sensor for the detection of Bi3+ and Fe3+ cations in water. (1st September 2021) - Wang, Guang-Qing; Huang, Xiao-Feng; Wu, Chu-Huang; Shen, Yong; Cai, Song-Liang; Fan, Jun; Zhang, Wei-Guang; Zheng, Sheng-Run
Graphical abstract: A hydrolytically stable hydrogen-bonded inorganic-organic network was obtained. The compound exhibits a turn-on luminescence sensing towards Fe 3+ and Bi 3+ ions in aqueous solutions with high sensitivity and selectivity. Abstract: Metal-organic materials capable of turn-on sensing of metal ions in water are highly desirable but relatively infrequently reported. Herein, a hydrogen-bonded inorganic-organic network based on Cu(I) ions and luminescent organic ligands, namely Cu-HBIBA (HBIBA = 4-[bis-(4-imidazol-1-ylphenyl)amino]benzoic acid), was synthesized and applied to detect trivalent metal ions (Fe 3+ and Bi 3+ ) in aqueous solution. Cu-HBIBA is a binuclear complex and exhibits an interesting hydrogen-bonded 1D → 2D polythreading array. Notably, Cu-HBIBA has good stability at pH values from 2 to 12 and is hardly soluble in aqueous solution. Cu-HBIBA shows luminescence enhancement in the presence of Fe 3+, and Bi 3+ ions and shows high selectivity and sensitivity with detection limits of 0.16 µM and 43 nM for Fe 3+ and Bi 3+, respectively. The hydrolytic stability, inhibited ligand-based luminescence and uncoordinated carboxylate groups in the network may contribute to the sensing performance of Cu-HBIBA. A mechanistic study indicates that the Cu-HBIBA crystal adsorbs metal ions via the carboxyl groups on its surface, leading to inhibition of the photoelectron transfer (PET) process, recovery of the luminescent emissions of the ligand and realization of turn-on luminescence detection.